Aggressive vertebral hemangioma presenting in postpartum period: A case report (Indian Journal of Case Reports, 2020)
Pregnancy is a known risk factor for hemangiomas to become aggressive and symptomatic. This is mainly because of the hormonal and hemodynamic changes and also due to increased intra-abdominal pressure. Vertebral hemangiomas usually become symptomatic in the third trimester. We present a rare case in which a young 20-year-old woman who remained asymptomatic during her pregnancy and presented with progressive paraparesis 5 days after vaginal delivery. Magnetic resonance imaging was done which revealed a vertebral hemangioma also involving the posterior elements, with soft-tissue extension in posterior epidural space. Surgery was done with removal of the soft tissue which was purely extradural in location. Histopathology revealed cavernous hemangioma.